Studies of Post-Fabrication Heat Treatment of L-PBF-Inconel 718: Effects of Hold Time on Microstructure, Annealing Twins, and Hardness - Wakshum M. Tucho; Vidar Hansen (Metals, 2021)
The widely adopted temperature for solid solution heat treatment (ST) for the conventionally fabricated Inconel 718 is 1100 °C for a hold time of 1 h or less. This ST scheme is, however, not enough to dissolve Laves and annihilate dislocations completely in samples fabricated with Laser metal powder bed fusion (L-PBF) additive manufacturing (AM)-Inconel 718. Despite this, the highest hardness obtained after aging for ST temperatures (970–1250 °C) is at 1100 °C/1 as we have ascertained in our previous studies. The unreleased residual stresses in the retained lattice defects potentially affect other properties of the material. Hence, this work aims to investigate if a longer hold time of ST at 1100 °C will lead to complete recrystallization while maintaining the hardness after aging or not. For this study, L-PBF-Inconel 718 samples were ST at 1100 °C at various hold times (1, 3, 6, 9, 16, or 24 h) and aged to study the effects on microstructure and hardness. In addition, a sample was directly aged to study the effects of bypassing ST. The samples (ST and aged) gain hardness by 43–49%. The high density of annealing twins evolved during 3 h of ST and only slightly varies for longer ST.